(Learning with a difference) English writing workshop: essential non-fiction - Ellison, Peter (Learners Publishing Singapore, 2007)
English Writing Workshop: Essential Non-Fiction is a practical guide designed for writers who want to hone their skills in creating compelling non-fiction. This workshop focuses on key elements such as research, structure, style, and voice, providing participants with tools to develop clear and engaging narratives. Through exercises and examples, the workshop encourages writers to explore various forms of non-fiction, including essays, articles, and memoirs. It emphasizes the importance of authenticity and effective storytelling, aiming to equip writers with the confidence and techniques needed to share their perspectives and experiences in a meaningful way.